Cognitive and Linguistic Factors Influencing Arabic Second Language Acquisition Among Adult Learners - Nasir Haman; Julia Einberg (IJAS: International Journal of Arabic Studies, 2025)
This study investigates the cognitive and linguistic factors that influence Arabic second language acquisition among adult learners. Drawing on data from multiple instructional contexts, the research explores how working memory capacity, attentional control, and metalinguistic awareness interact with linguistic features such as phonological complexity, orthographic processing, and root-and-pattern morphology. The findings reveal that both cognitive and linguistic factors strongly shape learners’ proficiency development, particularly in vocabulary acquisition, listening comprehension, and reading fluency. Learners with stronger cognitive abilities and greater morphological sensitivity demonstrated faster and more accurate processing of Arabic’s nonlinear linguistic structures. The study highlights the need for pedagogical approaches that integrate cognitive strategy training, explicit morphological instruction, and systematic phonological support to optimize learning outcomes. The results contribute to a deeper understanding of adult Arabic SLA and offer practical implications for curriculum development, instructional design, and technology-enhanced language learning.